The Relationship Between Water Quality and Stunting in Indonesia: Literature Review - Hasmy Raharini; Elsa Yuniarti (Postgraduate, University of Mataram, 2023)
A toddler who is stunting likely has a long-term nutritional problem since they are shorter than other children their age. Stunting is a problem that is brought on by environmental sanitation issues, such as water quality does not meet requirements. The purpose of this study is to summarize the existing research on the topic of the association between stunting and water quality in Indonesia. The Preferred Reporting Items for Systematic Review and Meta-Analysis (PRISMA) meta-analysis strategy is used in the study process together with the literature review methodology. If drinking water satisfies physical, microbiological, chemical, and radiological standards, it is safe for human consumption. Good water is defined as being no cloudy, tasteless, odorless, and colorless based on the physical criteria. Toddlers who drink clean water that is turbid or colored often get diarrhea. From some research results, there is a relationship between water quality and stunting in Indonesia. Toddlers will contract infectious infections that result in stunting if the drinking water quality does not match the standards.